2009
DOI: 10.1073/pnas.0809320106
|View full text |Cite
|
Sign up to set email alerts
|

Elevation increases in moth assemblages over 42 years on a tropical mountain

Abstract: Physiological research suggests that tropical insects are particularly sensitive to temperature, but information on their responses to climate change has been lacking-even though the majority of all terrestrial species are insects and their diversity is concentrated in the tropics. Here, we provide evidence that tropical insect species have already undertaken altitude increases, confirming the global reach of climate change impacts on biodiversity. In 2007, we repeated a historical altitudinal transect, origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
355
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(389 citation statements)
references
References 33 publications
18
355
2
5
Order By: Relevance
“…Fruitfeeding moths (Families Noctuidae and Geometridae) and butterflies (Family Nymphalidae) were sampled with traps baited with rotting banana, hung at stations at 100 m intervals along each transect. This guild comprises about 75 per cent of all nymphalid butterflies recorded on Borneo [64,65] but a much smaller proportion of noctuid and geometrid moths [66][67][68][69][70][71][72][73]. Traps were suspended 2 m above ground level at each station and fresh banana was added to the trap each day to ensure a mixture of fresh and well-rotted bait [74].…”
Section: Methods (A) Avian Responses To Fragmentation (I) Source Datamentioning
confidence: 99%
“…Fruitfeeding moths (Families Noctuidae and Geometridae) and butterflies (Family Nymphalidae) were sampled with traps baited with rotting banana, hung at stations at 100 m intervals along each transect. This guild comprises about 75 per cent of all nymphalid butterflies recorded on Borneo [64,65] but a much smaller proportion of noctuid and geometrid moths [66][67][68][69][70][71][72][73]. Traps were suspended 2 m above ground level at each station and fresh banana was added to the trap each day to ensure a mixture of fresh and well-rotted bait [74].…”
Section: Methods (A) Avian Responses To Fragmentation (I) Source Datamentioning
confidence: 99%
“…Reports of such adaptive variation and of shifts in species ranges and phenology illustrate the ability of some species to respond individualistically to significant climate change (Parmesan 2006). The following recent regional examples are informative: (1) Baltzer et al (2007Baltzer et al ( , 2008 describe current determinants of tree species distributions and the evolution of drought tolerance in trees north and south of the Kangar-Pattani Line; (2) Sheridan (2009) found three frog species that occur in both ever-wet Singapore and seasonal Thailand have adapted to the different environments with changes in clutch size, body size, and the timing of oviposition; (3) Round and Gale (2008) found that the lowland Siamese fireback pheasant Lophura diardi, has increased in abundance at higher elevations over 25 years in central Thailand; (4) Peh (2007) found evidence that other bird species have also extended their upper limits along elevation gradients; (5) Chen et al (2009) found that the average altitudes of individuals of 102 montane geometrid moth species on Mount Kinabalu in Borneo increased by 67 m between 1965 and 2007; (6) Corlett (2009b) discussed the innate dispersal abilities of trees and other plants and concluded that although altitudinal shifts are feasible as they involve short distances (a 3°C increase in mean annual temperature is equivalent to an elevational shift of *500 m), the required latitudinal range shifts, which may require dispersal of [500 km, and are unlikely to occur naturally in the time available; and (7) Bickford et al (2010) also discuss herpetological examples but argue that many regional amphibians and some reptiles will soon reach the physiological limits of their adaptability. Wright et al (2009) make the same point but more generally: tropical species are likely to be particularly sensitive to global warming because they are adapted to limited geographic and seasonal variation in temperature, already live at or near the highest temperatures on Earth before global warming began, and are often isolated from potential cool refugia.…”
Section: Patterns Of Distributionmentioning
confidence: 99%
“…Wilson et al 2005Wilson et al , 2007Moritz et al 2008). Within the tropics, because there is virtually no latitudinal temperature gradient between 218 N and 218 S, range shifts for terrestrial species can be expected to be almost exclusively upslope, where such shifts are topographically feasible and not interdicted by habitat fragmentation (Colwell et al 2008;Raxworthy et al 2008;Chen et al 2009). …”
Section: Interactions and Synergies: Riding With The Other Horsemenmentioning
confidence: 99%